2009
DOI: 10.4103/0256-4947.57173
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoepithelioma-like carcinoma of the urinary bladder: report of a rare case

Abstract: Lymphoepithelioma-like carcinoma (LELC) is a rare malignant neoplasm in the urinary bladder, which can histologically mimic lymphoma, poorly differentiated invasive transitional cell carcinoma or poorly differentiated squamous cell carcinoma with a lymphoplasmacytic background. A urinary bladder tumor was identified in a 65-year-old man suffering from hematuria for several weeks. Transurethral biopsy revealed an undifferentiated tumor with prominent lymphocytes and plasma cell infiltration. Immunohistochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
(34 reference statements)
0
6
0
Order By: Relevance
“… 4 Histological features of LELC closely resemble nasopharyngeal lymphoepithelioma, with the tumor growing in the nests, sheets, or cords of large undifferentiated malignant epithelial cells in the background of dense inflammatory infiltrate comprising mainly lymphocytes, plasma cells, and a few eosinophils and neutrophils. 1 Amin et al categorized LELC of the urinary bladder into three subgroups based on lymphoepithelioma component: pure (100%), predominant (> 50%), and focal (< 50%). These subgroups significantly determine the prognosis as disease-free survival is higher in pure and predominant LELCB than in mixed type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 Histological features of LELC closely resemble nasopharyngeal lymphoepithelioma, with the tumor growing in the nests, sheets, or cords of large undifferentiated malignant epithelial cells in the background of dense inflammatory infiltrate comprising mainly lymphocytes, plasma cells, and a few eosinophils and neutrophils. 1 Amin et al categorized LELC of the urinary bladder into three subgroups based on lymphoepithelioma component: pure (100%), predominant (> 50%), and focal (< 50%). These subgroups significantly determine the prognosis as disease-free survival is higher in pure and predominant LELCB than in mixed type.…”
Section: Discussionmentioning
confidence: 99%
“…Carcinomas with similar histological features arising outside the nasopharynx are known as LELC, which have been reported in various organs such as the thymus, cervix, and salivary glands. 1 Involvement of urinary bladder was first reported by Zukerberg et al in 1991 with a reported incidence between 0.4% and 1.3% of all bladder carcinomas. 2 It has been categorized into three subgroups: pure (100% lymphoepithelioma component), predominant (between 50% and 100%), and focal (< 50%).…”
Section: Introductionmentioning
confidence: 96%
“…They are revealed most of the time by haematuria, generally accompanied with urgency. These tumours have a favorable prognosis with a five-year survival of 59%, achieving 62% in the pure type, compared to transitional cell carcinoma [4]. They respond better to chemotherapy than transitional cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Although rates of metastases range from 10% to 15%, the present tumor was associated with a favorable prognosis and a 5-year survival of 59%, achieving 62% in the pure type [8]. The pure or predominant type responds better to chemotherapy than conventional urothelial carcinoma [5], and this provides a potential to salvage bladder function.…”
Section: Discussionmentioning
confidence: 99%